THE DOUBLE HELIX, A DOUBLE EDGED SWORD: ETHICAL ISSUES IN GENETIC TESTING AND RESEARCH - Anwar, Natasha (Journal of Postgraduate Medical Institute, 2013)
The DNA genome is unique in each one of us. It can tell us about our ancestors, our susceptibilityto disease, response to treatment and prognosis. Such complex information needs careful handling. How ittranslates into clinical practice and who has the right to access this information, is proving to be achallenge. It is very important to educate researchers on the impact of genetic research and itsconsequences for patients and for society as a whole1.The Ethical, Legal and Social Implications (ELSI) Research Program has identified three pivotalfactors currently shaping genomic research, its clinical translation, and its societal implications: (1) theincreasingly blurred boundary between research and treatment; (2) uncertainty - that is, the indefinite,indeterminate, and incomplete nature of much genomic information and the challenges that arise frommaking meaning and use of it; and (3) the role of negotiations between multiple scientific and nonscientificstakeholders in setting the priorities for and direction of biomedical research, as it is increasinglyconducted "in the public square"2.